2014
DOI: 10.22323/2.13010203
|View full text |Cite
|
Sign up to set email alerts
|

The passive voice in scientific writing. The current norm in science journals

Abstract: In contrast to past consensus, many authors now feel that the passive voice compromises the quality of scientific writing. However, studies involving scientific articles are rare. Using a corpus of 60 scientific research articles from six journals, this study examined the proportion of passives used, and the contexts and forms in which they occurred. The results revealed that about 30% of all clauses were passive clauses. The canonical form was most pervasive, followed by the bare passive; together, they const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…On the one hand, the predominant use of the passive voice by non-Anglophone authors was consistent with the study by Pérez-Llantada et al (2011), which extracted the opinion that there was a predilection for a heavy use of the passive among Spanish authors. Similarly, the present research has corroborated the conclusion by Alvin (2014) that the basic form would be the most common type of passive. But this study had contradicted the assertion by Hyland & Jiang (2017) that the scientific writing context would be dominated by conventions of formality with no influences of gender, status and other social features.…”
Section: Comparative Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…On the one hand, the predominant use of the passive voice by non-Anglophone authors was consistent with the study by Pérez-Llantada et al (2011), which extracted the opinion that there was a predilection for a heavy use of the passive among Spanish authors. Similarly, the present research has corroborated the conclusion by Alvin (2014) that the basic form would be the most common type of passive. But this study had contradicted the assertion by Hyland & Jiang (2017) that the scientific writing context would be dominated by conventions of formality with no influences of gender, status and other social features.…”
Section: Comparative Analysissupporting
confidence: 89%
“…On the temporal perspective, results from this study aligned with other studies (Seoane, 2013;Alvin, 2014;Hyland & Jiang, 2017) in finding a peak in the use of passives in scientific discourse by the end of the 20 th century. The present research confirmed the conclusions of those previous investigations, corroborating the theory that scientific texts would be turning to the active voice and impersonalisation and that this could be a sign of what Seoane (2013) defined as "the democratisation of the scientific discourse".…”
Section: Comparative Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Hundt et al claim that "academic style is more impersonal and thus more likely to make extensive use of agentless passives than fiction writing or newspaper language" (Hundt et al, 2016, 32). Others (Rodman, 1981;Halliday, 1988;Banks, 2008aBanks, , 2008bLeong Ping, 2014) have claimed that thematic structure is the basis of the use of the passive. The scientific writer, wishing to highlight the experiment or the object of study, places this in thematic, and therefore initial, position in the clause, where it will typically function as subject.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in writing a manuscript that is expected to be reviewed by publication, writers would be forced to deliberate their language more carefully in order to pass the evaluation (Silva, 2007). Moreover, studies have suggested that academic researchers employ specific uses of language at all levels including words (Coxhead, 2000), sentence structures (Alvin, 2014), and rhetorical moves (Swale, 2004). Therefore, it is not an easy task to complete an academic paper that is acceptable for journal publication.…”
Section: Introductionmentioning
confidence: 99%